Postpartum Yoga on Fitness Postpartum Mother - Arefti, Vyola Chania; Munah, Fauzul; Noviana, Ekki (Riviera Publishing, 2024)
Postpartum mothers experience physical and psychological changes, this greatly affects breast milk production and postpartum mother's fitness. Analyzing the effect of using the Postpartum Yoga movement on fitness in postpartum mothers and producing a proper Postpartum Yoga movement and its effective application so as to improve the welfare. quasi-experimental (Quasi Experiment Research) with Pre and Post Test approach with Control Group Design. This study involved a control group and a treatment group, 30 experimental and control groups of 30 respondents. The intervention given to the experimental group was postpartum yoga intervention 2 times for 2 weeks, while in the control group the standard of care for postpartum mothers was postpartum mothers who gave birth normally. The data were tested using the Wilcoxon test and the Mann-Whitney test. Postpartum yoga was effective in improving fitness (p-value 0.02) compared to the control group. Postpartum Yoga as an educational medium for holistic-based midwifery care during pregnancy and the puerperium, and its application is effective in improving fitness in postpartum mothers. It is recommended for postpartum mothers to use the Postpartum Yoga movement as an intervention to increase breast milk production and fitness in postpartum mothers.